一种纱线张力数字化仿真模型 - 邱海飞 (Jixie chuandong)
The CAD model of 6-bar shedding mechanism is set up in ADAMS/View,and the kinematics simulation analysis for it is carried out.Hookeanspring is used to substitute for actual yarn,and a virtual simulation platform which could simulate dynamic changes of yarn tension is created.The curve of yarn deflections and tension change are acquired through dynamic simulation,and the rationality and feasibility of the model is verified by comparing the simulation results with the measured results.In results,a new way of measuring yarn tension is offered.